Exploring New Structures of Kinase Inhibitors and Multitarget Strategies in Alzheimer's Disease Treatment - Tripathi, Siddhant; Sharma, Yashika; Kumar, Dileep (Protein and Peptide Letters, 2025)
Alzheimer's disease (AD) treatments currently available have ineffective results. Previously employed Acetylcholine esterase inhibitors and memantine, an NMDA receptor antagonist, target a single target structure that plays a complex role in the multifactorial progression of disease. Memantine moderates the toxic effects of excessive glutamate activity by blocking NMDA receptors, which decreases neurotoxicity in AD, while acetylcholine esterase inhibitors function by blocking cholinergic receptors (muscarinic and nicotinic), preventing the breakdown of acetylcholine, thereby enhancing cholinergic transmission, thus improving cognitive functions in mild to moderate stages of AD. Every drug class targets a distinct facet of the intricate pathophysiology of AD, indicating the diverse strategy required to counteract the advancement of this neurodegenerative disorder. Thus, patients are currently not getting much benefit from current drugs. A closer look at the course of AD revealed several potential target structures for future drug discovery. AD drug development strategies focus on developing new target structures in addition to well-established ones for combination treatment regimens, ideally with a single drug that can target two different target structures. Because of their roles in AD progression pathways like pathologic tau protein phosphorylations as well as amyloid β toxicity, protein kinases have been identified as potential targets. This review will give a quick rundown of the first inhibitors of single protein kinases, such as glycogen synthase kinase (gsk3) β, along with cyclin-dependent kinase 5. We will also look into novel inhibitors that target recently identified protein kinases in Alzheimer's disease, such as dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A). Additionally, multitargeting inhibitors, which target multiple protein kinases as well as those thought to be involved in other processes related to AD will be discussed. This kind of multitargeting offers prospective hope for improved patient outcomes down the road since it is the most effective way to impede multifactorial disease development.
Keywords: cyclin-dependent kinase 5